Computed Tomography Virtual Lab Software application in Biomedical Electronic Engineering Programme at University Malaysia Perlis - Zulkarnay, Zakaria; Mohd Hafiz, Fazalul Rahiman; Saidatul Ardeenawati, Awang; Nur Farahiyah, Mohamad; Azian Azamimi, Abdullah; Ruzairi, Abdul Rahim (Universiti Malaysia Perlis, 2010)
International Conference on X-Rays and Related Techniques in Research and Industry (ICXRI 2010) jointly organized by Universiti Malaysia Perlis (UniMAP) and X-Ray Application Malaysia Society (XAPP), 9th - 10th June 2010 at Aseania Resort Langkawi, Malaysia.